Acumulação de competências tecnológicas e os processos subjacentes de apredizagem: o caso da Invensys Appliance Controls - Unidade Vacaria - RS - Marin, Daniel Dionisio (2001)
This dissertation focuses on the relationship between the accumulation of technological capability and the underlying learning processes. This relationship was examined in the metalwork firm Invensys Appliance Controls Ltda in Unidade de VacariaIRS, during the period between 1981 and 2000. Based on individual case-study, three technological functions were studies: process and prodution organization, products and equipment. The underlying learning processes were examined in the ligth of four features: veriety, intensity, functioning and interaction. The firm originally began its activities based on technology acquired from other industries, and in that time lacked even of basic technological competence. As time passed by, it has acquired knowledge enough to develop and store its own competence through the subject learning process, which has influenced its story of technological competence accumulation. Using an analytical framwork available in the literature, but applying them to an industry different from previous studies, this dissertation concludes that the key characteristics of the subject learning process have played na essencial role on way and speed accumulation of technological competence in the firm